Evaluation of polyelectrolyte and emulsion covalent crosslink of chitosan for producing mesalasine loaded submicron particles (Brazilian Journal of Pharmaceutical Sciences, 2019)
This study evaluates various techniques for producing mesalamine (5ASA)-loaded particles employing chitosan as a biopolymer: (1) the polyelectrolyte complexation of chitosan with phthalate hypromelose (HP), (2) the chemical crosslinking of chitosan with genipin and (3) the water-in-oil emulsion method associated with chemical crosslinking with genipin. Systems were characterized by dynamic light scattering, zeta potential (ζ), powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR) and a drug release profile. Method (1) was efficiently produced unloaded nanoparticles (491 nm, PdI=0.26 and ζ = 23.2), but the conditions for chitosan and HP cross-linking enhanced the precipitation of 5ASA. Method (2) caused the degradation of the drug. Method 3 produced sub-micron and microparticles, thereby varying the agitation method; 3 h magnetic agitation resulted in 2692 nm, Pdi = 0.6 and ζ = 46, while Ultra-Turrax, 5 min produced submicron particles (537 nm, PdI = 0.6). The percentage yield was approximately 50%, which is very satisfactory considering the impossibility of encapsulating 5ASA using other methods. FTIR showed the covalent interaction of chitosan and genipin. The drug release was rapid in acidic fluid, but in neutral pH a slower release was obtained in the initial stage, followed by rapid release, which may ensure the controlled release of 5ASA in the colon.